VAT, Tariffs, and Withholding : Border Taxes and Informality in Developing Countries - Keen, Michael (IMF Working Papers; Working Paper ;, 2007)
This paper explores the implications of a distinctive feature of the value added tax (VAT) that is stressed by practitioners but essentially ignored by theorists: that it functions, in part, as a tax on the purchases of informal operators from formal sector businesses and, not least, on their imports. It stresses too the potential importance of the creditable withholding taxes that are levied by many developing countries-which have also been ignored. If both of these instruments are optimally deployed, it is shown, then the usual prescription that a small economy should not deploy tariffs remains valid even in the presence of an informal sector; and indeed a simple strategy is established-generalizing the standard prescription developed in models without informality-for deploying these instruments so as to preserve government revenue and increase welfare in the face of efficiency-improving tariff cuts. Conditions are established under which a VAT alone is fully optimal, precisely because it is in part a tax on informal sector production. But they are restrictive: more generally, an efficient tax structure requires deploying both a VAT and withholding taxes.